ENSURING HUMAN RIGHTS COMPLIANCE IN ADMINISTRATIVE DECISION MAKING: LESSONS FROM INDONESIAN CONSTITUTIONAL PRACTICE - Dirwansyah Dirwansyah; Cholidah Utama (Taksasila Edukasi Insani, 2025)
The protection of human rights in administrative decision making represents a crucial indicator of democratic governance and constitutional compliance. This study aims to examine the extent to which Indonesia’s administrative practices align with human rights principles as interpreted by the Constitutional Court. Using a qualitative juridical normative and analytical conceptual approach, the research analyzes Constitutional Court decisions, national legislation, and relevant scholarly literature. The findings reveal that while the Court has significantly contributed to embedding human rights norms into administrative law, its reasoning often oscillates between formalistic legality and substantive justice. Approximately 35% of the analyzed cases demonstrate progressive judicial reasoning that prioritizes proportionality and human dignity, while 45% remain confined to procedural legality. This dualism underscores the transitional nature of Indonesia’s constitutional adjudication toward a more rights-centered framework. The study concludes that sustainable human rights compliance requires stronger institutional mechanisms, inter agency coordination, and continuous human rights education for administrative officials.Keywords: administrative law, constitutional court, human rights, Indonesia, judicial reasoning